Preventing Bullying through the Experimental Ta’awun Program among Boarding School Students - Fitriah M. Suud; Faisal Bin Husen Ismail; Mirawati Mirawati; Tri Na'imah; Anniez Rachmawati Musslifah; Shinta Shinta; Sholawati Sholawati; Mohd Shafiq Bin Sahimi (Nazhruna: Jurnal Pendidikan Islam, 2025)
Prior research has demonstrated that bullying at Islamic boarding schools is a concerning issue, since it can hinder the psychological, social, and spiritual growth of students. Islamic boarding schools continue to report numerous incidents of bullying, encompassing verbal, physical, and social manifestations, despite their recognition as institutions that promote Islamic values. This study implemented a program to reduce bullying behaviour in a boarding school. This experimental study utilised both quantitative and qualitative methods, notably implementing a pretest-posttest design. Researchers selected a total of 30 students. The researchers gathered data by distributing a questionnaire designed to quantify the bullying variable. Following the data collection, the researchers implemented an intervention. Before the Ta'awun training intervention, researchers conducted a pretest to assess the students' baseline comprehension of bullying. Researchers utilised the pretest data to delineate the participants' status before the intervention. Researchers conducted a posttest in the last phase to evaluate the participants' knowledge of bullying following the intervention. The results indicated an 8.33% improvement in kids' comprehension of anti-bullying Ta'awun. The students successfully developed posters displaying the words "no bullying", accompanied by relevant drawings as a means of anti-bullying expression. Students preferred the Ta'awun anti-bullying program due to its comprehensive and collaborative approach, grounded in Islamic teachings. The students appreciated the Ta'awun anti-bullying initiative for its thorough and cooperative methodology, which is grounded in Islamic principles. Ta'awun training is designed with the student's well-being and the institution's needs in mind, so that participants can carry out their role as anti-bullying ambassadors with enthusiasm and without feeling burdened.